Dinamika Program Populis Terhadap Pengaruh Kebijakan Fiskal - Kunarso Kunarso; Enggar Dwi Hartono; Ragil Urip Raharjo; Moch Rofiuddin Mufaqih (INDO PUBLISHING, 2026)
The Populist Program is a program used by politicians as a political tactic to instantly win the hearts of the public. The Free Nutritious Meal Program (MBG) is a nationally scaled populist policy that, in its implementation, integrates Village Cooperatives (Kopdes) as the main pillar of the local food commodity supply chain. Although this partnership is strategically significant from an economic perspective, the integration brings complex legal implications within the business law landscape. This research aims to analyze the validity and standardization of the partnership contract between the MBG Management Agency and Kopdes, examine the readiness of Kopdes's corporate governance (Good Corporate Governance), and identify potential violations of fair business competition laws. The research method used is normative juridical with a statutory approach and a conceptual approach. Primary and secondary legal materials were qualitatively analyzed using the analytical lens of Law No. 25 of 1992 on Cooperatives, Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition, as well as government procurement regulations. The research results indicate that the partnership contract between MBG and Kopdes requires strict standardization of risk mitigation clauses, particularly concerning default risks in the supply chain and business dispute resolution mechanisms. From an institutional aspect, the surge in operational capital necessitates a reform of Kopdes' internal accountability to avoid legal risks in working capital financing. Furthermore, this study found that the designation of Kopdes as the sole aggregator has the potential to create business discrimination against non-cooperative SMEs. Therefore, a harmonious formulation of derivative regulations is needed to create an inclusive, accountable, and free from unfair business competition legal corridor for partnerships. Keywords: Free Nutritious Meals (MBG), Village Cooperatives, Business Law, Partnership Contracts, Business Competition.